Genus Datura: An Exploration of Genetic Alterations, Bioactive Compounds, and Pharmacological Activity - Khoirunnisa Assidqi; Nesti Fronika Sianipar; Dave Mangindaan; Chukwunwike Uchenna Enyi (Plants, 2025)
The genus Datura L. has pharmacological activities due to its source of bioactive compounds. The effects of bioactive compounds can vary depending on species, geographical location, and environmental conditions. The purpose of this review is to summarize the most recent progress and to provide a comprehensive overview of studies concerning genetic alteration and bioactive compounds in the genus Datura, based on Scopus publications between 2015 and 2025. Throughout history, the genus Datura (Solanaceae) contains nine species of medicinal plants. A key component of elucidating the diversification process of congeneric species is identifying the factors that encourage species variation. A comparative gene family analysis provides an understanding of the evolutionary history of species by identifying common genetic/genomic mechanisms that are responsible for species responses to biotic and abiotic environments. The diverse range of bioactive compounds it contains contributes to its unique bioactivity. Datura contains tropane alkaloids (such as hyoscyamine and scopolamine), datumetine, withametelin, daturaolone, and atropine. Several compounds have been isolated and refined for use in treating various conditions as a result of recent progress in therapeutic development. Daturaolone, for example, is used to treat certain neurological disorders. In addition to providing renewed opportunities for the discovery of new compounds, these advancements also provide insights into the genetic basis for their biosynthesis. Our discussion also includes pitfalls as well as relevant publications regarding natural products and their pharmacological properties. The pace of discovery of bioactive compounds is set to accelerate dramatically shortly, owing to both careful perspectives and new developments.